TREM-1 and TREM-2 as therapeutic targets: clinical challenges and perspectives - Sigalov, Alexander B. (Frontiers in Immunology, 2024)
Graphical AbstractTREM-1 and TREM-2 as Therapeutic Targets: Clinical Challenges and Perspectives.